The complex number z satisfying the equation $\left| {z - i} \right| = \left| {z + 1} \right| = 1$ is (This question has multiple correct options)
$
(a){\text{ 0}} \\
(b){\text{ 1 + i}} \\
(c){\text{ - 1 + i}} \\
(d){\text{ 1 - i}} \\
$
Answer
Verified
510.6k+ views
Hint: In this question we have to evaluate the equation given, so let the complex number Z satisfying this equation be of the form $x + iy$, where x is the real part and y is the imaginary part. Use the basic definition of $\left| z \right| = x + iy = \sqrt {{x^2} + {y^2}} $ along with the concept mentioned to get the right answer.
Complete step-by-step answer:
It is given z is a complex number so, let
$z = x + iy$
Given equation is
$\left| {z - i} \right| = \left| {z + 1} \right| = 1$
Now substitute the value of z in above equation we have,
$ \Rightarrow \left| {x + iy - i} \right| = \left| {x + iy + 1} \right| = 1$
$ \Rightarrow \left| {x + i\left( {y - 1} \right)} \right| = \left| {\left( {x + 1} \right) + iy} \right| = 1$
Now as we know $\left| {a + ib} \right| = \sqrt {{a^2} + {b^2}} $ so, use this property in above equation we have,
$ \Rightarrow \sqrt {{x^2} + {{\left( {y - 1} \right)}^2}} = \sqrt {{{\left( {x + 1} \right)}^2} + {{\left( y \right)}^2}} = 1$
Now squaring on both sides we have,
$ \Rightarrow {x^2} + {\left( {y - 1} \right)^2} = {\left( {x + 1} \right)^2} + {\left( y \right)^2} = {1^2}$
Now opening the whole square we have,
$ \Rightarrow {x^2} + {y^2} + 1 - 2y = {x^2} + 1 + 2x + {y^2} = 1$…………………. (1)
Now it is also written as
$ \Rightarrow {x^2} + {y^2} + 1 - 2y = {x^2} + 1 + 2x + {y^2}$
Now cancel out common terms we have,
$ \Rightarrow - 2y = 2x$
Divide by 2 we have,
$ \Rightarrow x = - y$ ……………. (2)
From equation (1)
$ \Rightarrow {x^2} + {y^2} + 1 - 2y = 1$
Now substitute the value of x in this equation we have,
$
\Rightarrow {\left( { - y} \right)^2} + {y^2} + 1 - 2y = 1 \\
\Rightarrow 2{y^2} - 2y = 0 \\
\Rightarrow {y^2} - y = 0 \\
\Rightarrow y\left( {y - 1} \right) = 0 \\
\Rightarrow y = 0,{\text{ & }}\left( {y - 1} \right) = 0 \\
$
$ \Rightarrow y = 0,1$
Now from equation (2)
$x = - y$
So, if y = 0 $ \Rightarrow x = 0$.
Now, if y = 1 $x = - 1$
So, the complex number
$z = x + iy = 0 + 0i = 0$
And $z = x + iy = - 1 + 1.i = - 1 + i$
Hence, option (a) and (c) is correct.
Note: Whenever we face such type of problems the key point is about the proper simplification of the equation part, since this is a multiple choice problem so be sure that you have evaluated all the possible values coming up for x and y and thus forming different complex numbers which will be satisfying the equation.
Complete step-by-step answer:
It is given z is a complex number so, let
$z = x + iy$
Given equation is
$\left| {z - i} \right| = \left| {z + 1} \right| = 1$
Now substitute the value of z in above equation we have,
$ \Rightarrow \left| {x + iy - i} \right| = \left| {x + iy + 1} \right| = 1$
$ \Rightarrow \left| {x + i\left( {y - 1} \right)} \right| = \left| {\left( {x + 1} \right) + iy} \right| = 1$
Now as we know $\left| {a + ib} \right| = \sqrt {{a^2} + {b^2}} $ so, use this property in above equation we have,
$ \Rightarrow \sqrt {{x^2} + {{\left( {y - 1} \right)}^2}} = \sqrt {{{\left( {x + 1} \right)}^2} + {{\left( y \right)}^2}} = 1$
Now squaring on both sides we have,
$ \Rightarrow {x^2} + {\left( {y - 1} \right)^2} = {\left( {x + 1} \right)^2} + {\left( y \right)^2} = {1^2}$
Now opening the whole square we have,
$ \Rightarrow {x^2} + {y^2} + 1 - 2y = {x^2} + 1 + 2x + {y^2} = 1$…………………. (1)
Now it is also written as
$ \Rightarrow {x^2} + {y^2} + 1 - 2y = {x^2} + 1 + 2x + {y^2}$
Now cancel out common terms we have,
$ \Rightarrow - 2y = 2x$
Divide by 2 we have,
$ \Rightarrow x = - y$ ……………. (2)
From equation (1)
$ \Rightarrow {x^2} + {y^2} + 1 - 2y = 1$
Now substitute the value of x in this equation we have,
$
\Rightarrow {\left( { - y} \right)^2} + {y^2} + 1 - 2y = 1 \\
\Rightarrow 2{y^2} - 2y = 0 \\
\Rightarrow {y^2} - y = 0 \\
\Rightarrow y\left( {y - 1} \right) = 0 \\
\Rightarrow y = 0,{\text{ & }}\left( {y - 1} \right) = 0 \\
$
$ \Rightarrow y = 0,1$
Now from equation (2)
$x = - y$
So, if y = 0 $ \Rightarrow x = 0$.
Now, if y = 1 $x = - 1$
So, the complex number
$z = x + iy = 0 + 0i = 0$
And $z = x + iy = - 1 + 1.i = - 1 + i$
Hence, option (a) and (c) is correct.
Note: Whenever we face such type of problems the key point is about the proper simplification of the equation part, since this is a multiple choice problem so be sure that you have evaluated all the possible values coming up for x and y and thus forming different complex numbers which will be satisfying the equation.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE